Community Preparadness For Earthquake Natural Disasters on Empirical Study - Solikhah, Mar’atus; Purwito, Dedy (Proceedings Series on Health & Medical Sciences, 2024)
Background: Indonesia is in a region prone to natural disasters, including earthquakes. Earthquakes often result in loss of life and property damage. One of the main factors contributing to a high casualty rate is the lack of knowledge, attitude, and behavior toward disasters and insufficient preparedness to anticipate such events. Method: A quantitative correlation study used a cross-sectional approach. The sample was selected using stratified random sampling, resulting in 16 samples from each educational level (elementary, junior high, high school, and university), totaling 64 respondents. Data analysis was conducted using the Chi-Square test. Results: The characteristics of the respondents of the gender, the most common are men 56.3%, the most common age group is in the 36-45 years old range 45.3%, then in the occupational group the most common are housewives with 26.6%. The study found that the majority of the community had sufficient knowledge (p-value 0.001), good attitudes (p-value 0.029), and sufficient behavior (p-value 0.001) towards earthquake preparedness. This indicates a significant relationship between the level of knowledge, attitude, and behavior with preparedness for earthquake natural disasters. Conclusion: Knowledge level, attitude, and behavior influence community preparedness for natural disasters, including earthquakes.